Tính:
a) \(\dfrac{3}{5} - \dfrac{{ - 1}}{3}\)
b) \( - 3 - \dfrac{2}{7}\)
Tính:
a) 4\(\dfrac{1}{3}\) + 2\(\dfrac{5}{6}\) b) 7 - 2\(\dfrac{2}{3}\) c) 2\(\dfrac{3}{7}\) x 1\(\dfrac{3}{4}\) d) 5\(\dfrac{1}{3}\) : 3\(\dfrac{1}{5}\)
a: \(=\dfrac{13}{3}+\dfrac{17}{6}=\dfrac{26}{6}+\dfrac{17}{6}=\dfrac{43}{6}\)
b: \(=7-\dfrac{8}{3}=\dfrac{21-8}{3}=\dfrac{13}{3}\)
c: \(=\dfrac{17}{7}\cdot\dfrac{7}{4}=\dfrac{17}{4}\)
d: \(=\dfrac{16}{3}:\dfrac{16}{5}=\dfrac{16}{3}\cdot\dfrac{5}{16}=\dfrac{5}{3}\)
Tính:
a) \(\dfrac{-7}{8}\) . \(\dfrac{3}{5}\) - \(\dfrac{2}{5}\) . \(\dfrac{7}{8}\) + \(3\dfrac{7}{8}\)
b) -1,6 : ( 1 + \(\dfrac{2}{3}\) )
c) \(\dfrac{6}{7}\) + \(\dfrac{5}{8}\) : 5 - \(\dfrac{3}{16}\) . ( -2 )\(^2\)
d) \(\dfrac{1^2}{1.2}\) . \(\dfrac{2^2}{2.3}\) . \(\dfrac{3^2}{3.4}\) . \(\dfrac{4^2}{4.5}\)
a: \(=\dfrac{-7}{8}\left(\dfrac{3}{5}+\dfrac{2}{5}\right)+3+\dfrac{7}{8}=\dfrac{-7}{8}+\dfrac{7}{8}+3=3\)
b: \(=-\dfrac{8}{5}:\dfrac{5}{3}=-\dfrac{24}{25}\)
c: \(=\dfrac{6}{7}+\dfrac{1}{8}-\dfrac{3}{4}=\dfrac{6}{7}+\dfrac{1}{8}-\dfrac{6}{8}=\dfrac{6}{7}-\dfrac{5}{8}=\dfrac{48}{56}-\dfrac{35}{56}=\dfrac{13}{56}\)
Tính:
a) \(\dfrac{5}{2}\times\dfrac{4}{3}+\dfrac{1}{3}\)
b) \(\dfrac{7}{3}-\dfrac{2}{3}:\dfrac{5}{7}\)
c) \(\dfrac{3}{4}\times\left(\dfrac{5}{2}-\dfrac{3}{2}\right)\)
a) $\frac{5}{2} \times \frac{4}{3} + \frac{1}{3} = \frac{{10}}{3} + \frac{1}{3} = \frac{{11}}{3}$
b) $\frac{7}{3} - \frac{2}{3}:\frac{5}{7} = \frac{7}{3} - \frac{2}{3} \times \frac{7}{5} = \frac{7}{3} - \frac{{14}}{{15}} = \frac{{35}}{{15}} - \frac{{14}}{{15}} = \frac{{21}}{{15}} = \frac{7}{5}$
c) $\frac{3}{4} \times \left( {\frac{5}{2} - \frac{3}{2}} \right) = \frac{3}{4} \times 1 = \frac{3}{4}$
Tính:
a) \(\dfrac{1}{7}+\dfrac{2}{7}+\dfrac{3}{7}\) b) \(\dfrac{2}{9}+\dfrac{5}{9}+\dfrac{8}{9}\)
c) \(\dfrac{13}{14}-\dfrac{5}{14}-\dfrac{1}{14}\) d) \(\dfrac{7}{11}-\dfrac{4}{11}-\dfrac{3}{11}\)
Tính:
a) \(\dfrac{2}{5}\times\dfrac{3}{8}\times\dfrac{3}{4}\) b) \(\dfrac{1}{3}\times\dfrac{1}{6}\times\dfrac{1}{9}\)
c) \(\dfrac{3}{4}:\dfrac{1}{5}:\dfrac{7}{8}\) d) \(\dfrac{3}{5}:\dfrac{1}{5}:\dfrac{1}{8}\)
a) $\frac{2}{5} \times \frac{3}{8} \times \frac{3}{4} = \frac{{2 \times 3 \times 3}}{{5 \times 8 \times 4}} = \frac{{18}}{{160}} = \frac{9}{{80}}$
b) $\frac{1}{3} \times \frac{1}{6} \times \frac{1}{9} = \frac{{1 \times 1 \times 1}}{{3 \times 6 \times 9}} = \frac{1}{{162}}$
c) $\frac{3}{4}:\frac{1}{5}:\frac{7}{8} = \frac{3}{4} \times \frac{5}{1} \times \frac{8}{7} = \frac{{3 \times 5 \times 8}}{{4 \times 1 \times 7}} = \frac{{120}}{{28}} = \frac{{30}}{7}$
d) $\frac{3}{5}:\frac{1}{5}:\frac{3}{8} = \frac{3}{5} \times \frac{5}{1} \times \frac{8}{3} = \frac{{3 \times 5 \times 8}}{{5 \times 1 \times 3}} = 8$
Tính:
a) \(\sqrt{\dfrac{9}{16}}-\dfrac{5}{6}+\dfrac{3}{2}\) b) \(\left(\dfrac{1}{9}+\dfrac{2}{3}\right)^2-\dfrac{5}{3}:\sqrt{25}\)
c)\(\dfrac{5}{11}.\left(-\dfrac{3}{7}\right)+\dfrac{5}{11}.\left(\dfrac{-5}{7}\right)+\left(-\dfrac{8}{7}\right).\dfrac{6}{11}\)
d) \(\dfrac{2^8.2^{18}}{8^5.4^6}\)
a: \(=\dfrac{3}{4}-\dfrac{5}{6}+\dfrac{3}{2}=\dfrac{9-10+18}{12}=\dfrac{17}{12}\)
b: \(=\left(\dfrac{1}{9}+\dfrac{6}{9}\right)^2-\dfrac{1}{3}=\dfrac{49}{81}-\dfrac{27}{81}=\dfrac{22}{81}\)
c; \(=\dfrac{5}{11}\left(-\dfrac{3}{7}-\dfrac{5}{7}\right)+\dfrac{-8}{7}\cdot\dfrac{6}{11}=\dfrac{-8}{7}\left(\dfrac{5}{11}+\dfrac{6}{11}\right)=-\dfrac{8}{7}\)
d: \(=\dfrac{2^{26}}{2^{15}\cdot2^{12}}=\dfrac{1}{2}\)
Tính:
a) \(\dfrac{2}{3}\times\dfrac{5}{8}+\dfrac{7}{4}\) b) \(\dfrac{8}{5}:\left(\dfrac{4}{3}-\dfrac{5}{6}\right)\) c) \(\dfrac{3}{4}\times\dfrac{1}{5}-\dfrac{1}{10}\)
a) $\frac{3}{2} \times \frac{5}{8} + \frac{7}{4} = \frac{{15}}{{16}} + \frac{7}{4} = \frac{{15}}{{16}} + \frac{{28}}{{16}} = \frac{{43}}{{16}}$
b) $\frac{8}{5}:\left( {\frac{4}{3} - \frac{5}{6}} \right) = \frac{8}{5}:\left( {\frac{8}{6} - \frac{5}{6}} \right) = \frac{8}{5}:\frac{1}{2} = \frac{8}{5} \times 2 = \frac{{16}}{5}$
c) $\frac{3}{4} \times \frac{1}{5} - \frac{1}{{10}} = \frac{3}{{20}} - \frac{1}{{10}} = \frac{3}{{20}} - \frac{2}{{20}} = \frac{1}{{20}}$
Tính:
a) \(\dfrac{7}{3}+\dfrac{4}{9}\) b) \(\dfrac{3}{14}+6\) c) \(\dfrac{7}{8}-\dfrac{1}{2}\) d) \(5-\dfrac{9}{10}\)
a: \(\dfrac{7}{3}+\dfrac{4}{9}=\dfrac{21}{9}+\dfrac{4}{9}=\dfrac{21+4}{9}=\dfrac{25}{9}\)
b: \(\dfrac{3}{14}+6=\dfrac{3+6\cdot14}{14}=\dfrac{84+3}{14}=\dfrac{87}{14}\)
c: \(\dfrac{7}{8}-\dfrac{1}{2}=\dfrac{7}{8}-\dfrac{4}{8}=\dfrac{7-4}{8}=\dfrac{3}{8}\)
d: \(5-\dfrac{9}{10}=\dfrac{50}{10}-\dfrac{9}{10}=\dfrac{50-9}{10}=\dfrac{41}{10}\)
Tính:
a) \(\dfrac{3}{8}+\dfrac{7}{8}\) b) \(\dfrac{7}{9}-\dfrac{4}{9}\) c) \(\dfrac{5}{6}+\dfrac{1}{8}\) d) \(\dfrac{9}{15}-\dfrac{2}{5}\)
e) \(\dfrac{2}{5}+\dfrac{3}{5}+\dfrac{9}{5}\) g) \(\dfrac{8}{10}-\dfrac{1}{10}-\dfrac{3}{10}\) h) \(\dfrac{23}{7}-\dfrac{4}{7}+\dfrac{2}{7}\)
a: \(\dfrac{3}{8}+\dfrac{7}{8}=\dfrac{3+7}{8}=\dfrac{10}{8}=\dfrac{5}{4}\)
b: \(\dfrac{7}{9}-\dfrac{4}{9}=\dfrac{7-4}{9}=\dfrac{3}{9}=\dfrac{1}{3}\)
c: \(\dfrac{5}{6}+\dfrac{1}{8}=\dfrac{20}{24}+\dfrac{3}{24}=\dfrac{20+3}{24}=\dfrac{23}{24}\)
d: \(\dfrac{9}{15}-\dfrac{2}{5}=\dfrac{3}{5}-\dfrac{2}{5}=\dfrac{3-2}{5}=\dfrac{1}{5}\)
e: \(\dfrac{2}{5}+\dfrac{3}{5}+\dfrac{9}{5}=\dfrac{2+3+9}{5}=\dfrac{14}{5}\)
g: \(\dfrac{8}{10}-\dfrac{1}{10}-\dfrac{3}{10}=\dfrac{8-1-3}{10}=\dfrac{4}{10}=\dfrac{2}{5}\)
h: \(\dfrac{23}{7}-\dfrac{4}{7}+\dfrac{2}{7}=\dfrac{23-4+2}{7}=\dfrac{21}{7}=3\)